2017
DOI: 10.3923/pjbs.2017.197.203
|View full text |Cite
|
Sign up to set email alerts
|

Flavonoid Production, Growth and Differentiation of Stelechocarpus burahol (Bl.) Hook. F. and Th. Cell Suspension Culture

Abstract: The results show that flavonoid production, growth and cell differentiation of a S. burahol cell suspension culture differed according to the culture age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Kinetin significantly increased the growth and differentiation of callus D. alata propagated in vitro with an optimal concentration of 2.5 mg/L [19]. Furthermore, 2,4-D acts like auxin, significantly affecting plant calluses' growth, such as Stelechocarpus burahol [20] and Elaeocarpus grandiflorus [21]. However, the effect of the 2,4-D mechanism on D. esculenta callus growth remains unclear.…”
Section: Resultsmentioning
confidence: 99%
“…Kinetin significantly increased the growth and differentiation of callus D. alata propagated in vitro with an optimal concentration of 2.5 mg/L [19]. Furthermore, 2,4-D acts like auxin, significantly affecting plant calluses' growth, such as Stelechocarpus burahol [20] and Elaeocarpus grandiflorus [21]. However, the effect of the 2,4-D mechanism on D. esculenta callus growth remains unclear.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have reported that 8 th weeks of Taraxacum officinale during exponential growth produced higher triterpene yield than stationary phase (Martínez et al, 2023). Furthermore, flavonoid production from Stelechocarpus burahol cell suspension culture showed higher yield during the cell growth in the log phase (Habibah et al, 2017). Based on our best knowledge, there is no information regarding the effect of callus age (growth phase) on flavonoid production in Talinum paniculatum in vitro culture.…”
Section: Introductionmentioning
confidence: 88%
“…This is might be in the exponential phase, the callus is actively dividing and increasing biomass so that in this phase the flavonoids synthesized are also higher (Tan et al, 2010). Furthermore, Habibah et al (2017) also reported that flavonoid production from Stelechocarpus burahol cell suspension culture showed higher yield during the cell growth in the log phase than stationary phase. This research also reported that the production of flavonoids in the cell suspension cultures of S. burahol was not in line with its growth.…”
Section: Jurnal Pembelajaran Dan Biologimentioning
confidence: 96%
“…Ex situ conservation attempts using in vitro culture can be used to effectively propagate this plant. Several studies related to in vitro culture of Kepel plants have been conducted with several focuses, including optimization of sterilization methods for leaf explants (Habibah et al, 2013), nodes (Hutabarat et al, 2022) and endosperm (Handayani et al, 2022), optimization of PGR that supports callus growth of Kepel seed and fruit mesocarp explants (Habibah et al, 2016(Habibah et al, , 2017(Habibah et al, , 2019, and nodal explant (Sekar et al, 2023), and optimization of flavonoid production from callus and cell suspension cultures of Kepel plants (Habibah et al, 2016(Habibah et al, , 2019. However, in vitro propagation of Kepel plants still faces obstacles, including the browning of explants.…”
Section: Introductionmentioning
confidence: 99%